Difficulties of teaching Ukrainian as a foreign language in a bilingual environment - Kryvolapova, O. V. (Видавничий дім "Гельветика", 2020)
This article is devoted to the problem of bilingualism; the affects of this situation on the state of education of international students in Ukrainian universities are considered. Many linguists were interested in the problem of bilingualism and ways to solve it. One of the first who developed the theory of bilingualism was L. V. Shcherba. He distinguished between two types of bilingualism: pure and mixed ones. Pure bilingualism implies the complete isolation of one language from the other. Mixed bilingualism means the parallel use of two languages. Of course, the language environment of many Ukrainian cities, including Kharkiv, is determined by mixed bilingualism. Considering the problem of bilingualism, it is impossible not to touch on such a phenomenon as interlingual interference. In linguistics, the term “interference” means the effects of one language on another, that is, the rules of one language are applied in the written or oral speech of the other one. Unfortunately, this often leads to the fact that interlingual interference can cause many inaccuracies. This paper gives some examples of such errors from which we can conclude that it is the interference that explains the phonetic, grammatical and lexical features manifested in a bilingual environment. In addition, the situation of bilingualism is never harmonious or symmetrical. This means that in language practice, one of the communicating languages necessarily occupies a leading position. The article also expresses the opinion that in the conditions of Russian-Ukrainian bilingualism, it is the interference that can explain such a linguistic phenomenon as Surzhyk. Currently, this term is firmly established in Ukrainian linguistics. Scientists have not yet reached a single conclusion about the origin and essence of this phenomenon, but one thing is certain: Surzhyk is the result of mixing exactly two languages: Ukrainian and Russian. Having analyzed the situation of bilingualism in the Kharkiv region, we can conclude that bilingualism makes things more difficult for international students: for both those who study Ukrainian and those who study English. Students need to master the basics of a second language to adapt in a bilingual environment.

Статтю присвячено проблемі білінгвізму (двомовності); розглянуто, як впливає така ситуація на стан навчання іноземних студентів в українських вишах. Проблемою білінгвізму і способами її вирішення цікавилися багато лінгвістів. Одним із перших, хто розробив теорію білінгвізму, був Л. В. Щерба. Він розрізняв два типи двомовності: чисту і змішану. Чиста двомовність передбачає повну ізоляцію однієї мови від іншої. Змішана означає паралельне вживання двох мов. Звичайно ж, мовне середовище багатьох українських міст, у тому числі й Харкова, визначає саме змішана двомовність. Розглядаючи проблему білінгвізму, не можна не торкнутися такого явища, як міжмовна інтерференція. У мовознавстві термін "інтерференція" означає наслідки впливу однієї мови на іншу, тобто норми однієї мови застосовуються в письмовому або усному мовленні іншої. На жаль, це часто призводить до того, що міжмовна інтерференція може стати причиною безлічі неточностей. У даній роботі наведено приклади таких помилок, з чого можна зробити висновок, що саме інтерференцією пояснюються фонетичні, граматичні та лексичні особливості, які проявляються у двомовному середовищі. Крім того, ситуація білінгвізму ніколи не буває гармонійною або симетричною. Це означає, що в мовній практиці одна з тих мов, що контактують, обов'язково займає чільну позицію. У статті також висловлено думку про те, що в умовах російсько-української двомовності саме інтерференцією можна пояснити таке мовне явище, як суржик. Натепер цей термін міцно затвердився в українському мовознавстві. Науковці ще не дійшли єдиного висновку щодо виникнення і сутності цього явища, але незаперечно одне: суржик – це наслідок змішування саме двох мов: української та російської. Проаналізувавши ситуацію білінгвізму в Харківському регіоні, можна зробити висновок, що двомовність дуже ускладнює становище іноземних студентів: як тих, хто вивчає українську мову, так і тих, хто вивчає англійську. Студенти мають потребу в оволодінні основ другої мови для адаптації у двомовному середовищі.
Труднощі викладання української мови як іноземної у двомовному середовищі
Keywords: bilingualism; language environment; interlingual interference; related languages; language adaptation; Surzhyk; білінгвізм; мовне середовище; міжмовна інтерференція; споріднені мови; мовна адаптація; суржик